A taxonomic review of Odontogryllodes Chopard, 1969 (Gryllidae: Landrevinae) - Tan, Ming Kai; Muhammad, Amira Aqilah; Abdullah, Nurul Ashikin; Japir, Razy; Chung, Arthur Y.c. (Zootaxa, 2024)
The taxonomy of the crickets from the genus Odontogryllodes Chopard, 1969 is reviewed. Two species new to science are described here, one from Peninsular Malaysia (part of Malay Peninsula) and another from East Malaysia (part of Borneo): Odontogryllodes undatus Tan, Muhammad & Abdullah sp. nov. from Panti Forest Reserve and Odontogryllodes magnus Tan, Japir & Chung sp. nov. from Tenompok Forest Reserve, respectively. We also present an updated key to the species of Odontogryllodes. In total, nine species are currently known.